Intelligent remote health monitoring system. (4th January 2021) - Basu, Samik; Ghosh, Mahasweta; Mandal, Soma Barman
With more than 45% of WHO member states failing to achieve the WHO standard of 1:1000 doctor to patient ratio; under current scenario intelligent and remote self-health monitoring becomes too vital for regular health monitoring of people. Rural people have even less doctor to patient ratio than urban people and so cost-effective intelligent vital sign monitoring system becomes even more essential. In our proposed system, we have used sensors to monitor vital health parameters like heart rate, SpO2 and body temperature and upload this information to the cloud server, using IoT platform, for remote access to the doctors. In case of non-availability of internet services, the proposed system is capable of predicting the cardiac health condition of the person independently by using machine learning algorithm. E-mail and health indicator unit alert the person at the remote-end and system-end respectively in case of emergencies.